PENERAPAN ARSITEKTUR PERILAKU PADA REDESAIN PASAR SENTRAL SUDU DI KABUPATEN ENREKANG - Muhammad Chaidar Febriansyah; Burhanuddin Burhanuddin; Musytahidah Musytahidah (Jurnal PROYEKSI: Arsitektur dan Perencanaan, 2022)
The Central Market of Sudu is the traditional markets which is located in Enrekang Regency and has become the pillars of the Enrekang Regency economy which was built and managed by the Regional Government. The condition of the market is currently being faced with various problems or obstacles in order to realize comfort and safety for its users. To respond the problems, it is necessary to carry out a strategy with redesign applications as an effort to improve the existing conditions to be better, safer and more comfortable central market to accommodate all economic activities in it, which is behavioral architecture is part of the design completion. In this study, the method used for data collection was mixed methods with data mining using behavioral mapping methods. Behavioral architecture as a design strategy to solve the problems of the Sudu Central Market which aims to create a market environment that is adapted to the human behavior of its users, which emphasizes the aspects of physical and psychological comfort.